Socialization and its relationship to the phenomenon of violence in sports, and the role of sports media. - Saeed Mohsen, Abdul Jabbar (sports creativity, 2025)
All the humanities are concerned with studying social phenomena, which means studying human actions and behaviors that exist to a certain degree of prevalence in a particular society at a particular time. The actions and behaviors that constitute an element of a social phenomenon must be characterized by generality and prevalence; that is, they are the actions of the majority of the society. Herein lies the fundamental question: Are generality, prevalence, and human actions and behaviors absolute or relative concepts? In other words, do generality, prevalence, actions, and behaviors differ according to society, time, and place? The actions and behaviors that constitute social phenomena can be viewed on two levels. The first level pertains to those actions and behaviors that are free from the constraints of time and place, and these are what distinguish humans as social beings. The second level refers to actions and behaviors influenced by time, and these are what distinguish one society from another, whether through customs, traditions, norms, or methods of social organization (Mujib et al., 1961). We must consider humans as living beings with animalistic characteristics, and this perspective prioritizes material motives in life over secondary ones. Humans have interacted with their geographical environment and with others through ideas, symbols, and surrounding objects, ultimately creating their own culture, which is the essence of their distinction from animals, who cannot create their own culture. Therefore, social behavior does not predate human existence, as humans themselves created it.